Functional Bowel Disorder Management in Routine Practice with Tips for Hot Topics: Expert Opinion Review - Akyüz, Filiz; Çelebi, Altay; Doğan, İbrahim; Erzin, Yusuf; Kav, Taylan; Soytürk, Müjde; Oğuz, Dilek; Özer, Birol; Kaymakoğlu, Sabahattin (Turkish Journal of Gastroenterology, 2024)
Functional gastrointestinal system disorders are common problems in practice. The most common symptoms are abdominal pain, gas, bloating, diarrhea, constipation, and a mixture of these, and similar symptoms can be seen in conditions such as inflammatory bowel disease, colorectal cancer, and celiac disease depending on the age of the patient, indicating the importance of differential diagnosis. The importance of patient management is shown by making a symptom-based diagnosis and making cost-effective, that is, limited advanced examinations. The pathophysiology of irritable bowel syndrome (IBS) is multifactorial, and stress is one of the leading triggers of IBS symptoms. Therefore, terminology will change to gut–brain interaction disorders in the future, and the patient–physician relationship has a special place in the treatment of functional bowel disorder. Dietary recommendation and medical treatment in IBS should be determined according to the predominant symptom and symptom severity. In addition to diet, some lifestyle changes can also be helpful in reducing IBS symptoms. Antispasmodics and antidepressants are not fast-acting. These drugs should be used for at least 2-4 weeks to see the efficacy of treatment. Drugs should be used according to the standard recommended duration and dose in intermittent treatments. Cite this article as: Akyüz F, Çelebi A, Doğan İ, et al. Functional bowel disorder management in routine practice with tips for hot topics: Expert opinion review. Turk J Gastroenterol. 2024;35(6):423-439.